DECISION SUPPORT SYSTEM FOR SELECTION OF OUTSTANDING PROSPECTIVE STUDENTS AT SMKS AL WASHLIYAH 2 MERBAU SCHOOL USING PROFILE MATCHING - Sabina Wardaniah; Hijka Listia; Siti Wulandari; Debi Yandra Niska (Jurnal Riset Informatika, 2025)
The selection of outstanding students in the school environment is an important process that requires objective and structured assessment. However, in practice, this process is still often done manually so that it has the potential to cause subjectivity and inaccuracy in decision making. This study aims to build a Decision Support System (DSS) in the selection of prospective outstanding students at SMKS Al-Washliyah 2 Merbau using the Profile Matching method. This method works by comparing the competencies or criteria possessed by students with the ideal profile that has been determined so that the gap (difference) between the two can be identified. The criteria used in the assessment include academic aspects, organizational activity, personality and discipline. This system is implemented in the form of a computer-based application to facilitate the selection process and improve assessment accuracy. The implementation of Decision Support using the Profile Matching method can be concluded that the system built is able to provide an effective solution in the selection process of prospective outstanding students at SMKS Al-Washliyah 2 Merbau.